Aktualisasi Nilai-Nilai Pancasila dalam Kehidupan Berbangsa dan Bernegara di Era Generasi Milenial - Chitra Wahyu Mulyaningrum; Iqbal Bagas Pratama; Nadia Ria Oktavia; Riska Andi Fitriono (Fakultas Hukum, Universitas Diponegoro, 2022)
The dynamics in actualizing the values of Pancasila in the life of the nation and state in the era of the millennial generation is a form of necessity, so that Pancasila is always aligned in its function to provide guidance in the life of the nation and state as a policy-making and solving problems. Pancasila values have been inculcated since childhood, but if they are not studied and understood, they will easily fade. The millennial era is currently in the midst of the swift currents of western globalization. Pancasila values should be engraved in the spirit and brain of the ongoing millennium. The implied values contained in Pancasila are key in regulating individual behavior and mentality.